Polyethylene Wear in Knee Arthroplasty - Chakravarty, Rajit; Elmallah, Randa D. K.; Cherian, Jeffrey Jai; Kurtz, Steven M.; Mont, Michael A. (The Journal of Knee Surgery, 2015)
Polyethylene (PE) wear and osteolysis are common causes for late revisions of knee arthroplasties. Several implant and surgical factors have been implicated in contributing to the development of wear, such as type of bearing surface used, inaccurate articular geometry, and poor knee kinematics. In addition, patient-related factors, such as younger age and higher activity levels, may also contribute to wear. Our purpose was to evaluate and compare the effect of these variables on wear rates following knee arthroplasty. Recently, technological advancements have been aimed at reducing the incidence of wear by improving the PE manufacturing process, creating implants that minimize contact stresses, and refining our surgical techniques. Furthermore, the development of newer highly cross-linked PEs (HXLPEs) and the introduction of additives, such as vitamin E, to the PEs may improve overall implant survivorship. As a result, with the advent of newer implant and PE designs, wear is no longer the most common cause of early failure, though it remains an important factor in limiting long-term implant survivorship. However, there are a few clinical studies evaluating the long-term outcomes of newer HXLPEs and implant designs, with further evaluations necessary to determine the best implant–PE combination for improved knee arthroplasty survivorship.
Keywords: knee arthroplasty; polyethylene; wear; TKA; knee arthroplasty